Harmonisasi Hukum dalam Perspektif Perundang-Undangan - Kusnu Goesniadhie Slamet (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The special agency in accordance to Banking Law Number 10/1998 is an agency put forward to settle and torecover state funds formerly placed in the banking industries in time of severe economic crisis. The special agency has given a broad power to this agency evensurpass the power or authority that normally become the power of the court. This regulation is one example of how some times Indonesian regulations are notin harmony to each others and become a stumble block in establishing due process of law, giving fair treatment and establishing good system of law. it is also now on derif the effectiveness ofthis special regulation and the functions ofthe specialagency it is created do not meet the requirement insettling government financial problem.The purpose of this paperisto determine whetherthe existing regulations arein harmony each other, to analyze which regulation should putinplace or which one shouldbe remove, which theory orprinciple can be put forward orkept as the basic argumentation in creating harmonious law.To be particularitis recommended that based upon consideration using normative analytical method on dogmatic legal system to create harmoni ous lawin Indonesia, there mustbe a new law in banking namely, 'undang-undang penyelesaian bank bermasalah' which permanently become the guidance ofany agency which its functions is tosettle banking problem.